Does classroom matter? - A longitudinal multilevel perspective on students' achievement goal orientation profiles during lower secondary school. (June 2023) - Ketonen, Elina E.; Hienonen, Ninja; Kupiainen, Sirkku; Hotulainen, Risto
Abstract: The present study adds to earlier person-oriented research by investigating differences in students' achievement goal orientation (AGO) profiles and their development using a simultaneous consideration of classroom patterns with longitudinal multilevel methods. The sample of almost 10, 000 lower secondary school students, representing over 600 classrooms, was surveyed on their AGOs in the 7th and 9th grade. Multilevel latent profile analyses (MLPAs) and transition analysis (MLTA) revealed similar student profiles in AGOs in both grades: success-oriented, moderate multiple goals and avoidance-oriented, as well as two classroom types: success-oriented and mixed orientation classrooms with varied relative proportions of different student-level profiles and patterns of likely transitions. Stability of profiles was more typical than change. Maladaptive transitions were related to lower, and stable and adaptive transitions to higher GPA in the end of 9th grade. In success-oriented classrooms, it was more common to maintain or adopt the success-orientation across lower secondary school compared to the other classroom type. Highlights: We examined achievement goal profiles using multilevel latent transition analysis. Three parallel student-level and two class-level profiles were found across time. Stability of student profiles from 7th to 9th grade was more typical than change. Stable and adaptive transitions related to higher GPA, maladaptive changes to lower GPA. Proportions of student profiles, stability and change depended on classroom profile.